The society of information and the European citizens’ perception of climate change: Natural or anthropological causes - Mata, F.; Dos-Santos, M.; Cano-Díaz, C.; Jesus, M.; Vaz-Velho, M. (Environmental Management, 2025)
TThe scientific community has reached a consensus on humans’ important role as causative agents of climate change; however, branches of society are still sceptical about this. Climate change is a key issue for humanity and only the commitment to change human attitudes and lifestyles, at the global level, can be effective in its mitigation. With this purpose, it is important to convey the right message and prevent misinformation to manipulate people’s minds. The present study aims to understand the factors shaping European citizens’ thoughts on the causes of climate change. Using data from the European Social Survey 10 collected in 2022, we fitted statistical models using the people’s thoughts on causes of climate change (natural, anthropogenic or both) as dependent variables. As independent variables, we used the impact of the media through time spent on news and time spent on the internet, level of education, level of trust in scientists, awareness of online or mobile misinformation and gender. We concluded that the typical European citizen who believes in anthropogenic causes of climate change is a female, is more literate, trusts more in scientists, is younger, spends more time reading the news and has more awareness of misinformation presence in online and mobile communications.